Today`s talented youth field hockey players, the stars of tomorrow? A study on talent development in field hockey - Elferink-Gemser, M. T. (2005)
The aim of the thesis was addressed by conducting research within a group of all talented field hockey players, measuring multidimensional performance characteristics in a sports-specific way, and following talented players across time by adopting a longitudinal study design. With caution because the talented players from this study have not yet reached expert performance in adulthood, and with acknowledging the limitations of this study, it is concluded that a talented field hockey player with the greatest chance of succeeding is a player with a relatively high level of performance in field hockey specific physiological characteristics, excellent technical skills, excellent tactical skills, and a very high motivation at the age of fourteen already. This, however, is not enough. A player also has to have potential to reach elite status in the future. Elite players need less time to develop better performance characteristics, meaning that a talented player has to increase his or her performance characteristics at a relatively fast pace for many years in a row. To sustain the long road to the top, investing enormous amounts of time preparing for the international sporting arena, again motivation is essential. From this thesis, relevant information for trainers, coaches, scouts, players, parents and other field hockey enthusiastics can be given: - Acknowledge the multidimensional nature of a field hockey performance: a talented player is more than a technically gifted player. - Motivation plays an essential role in the development of a successful career in field hockey. - Technical and especially tactical skills have to be excellent if a player is to succeed. - In addition, a talented player needs a relatively high level of field hockey specific physiological characteristics: sprinting fast over short distances, perform these sprints repeatedly, is agile while sprinting, and has a great interval endurance capacity. For each talented player, it is recommended to construct a performance profile repeatedly, i.e. every year, during the entire process of talent development. In this way, the player`s level of performance characteristics can be compared to other talented peers. Even more, his or her development of the performance characteristics across time can be recorded. This performance profile can be constructed by measuring the multidimensional performance characteristics with the field hockey test battery from this study. In Vakblad Hockey, an electronic journal of the Dutch Field Hockey Association, reference data of the multidimensional performance characteristics of talented boys and girls under 14 years, under 16 years, and under 18 years are published (Elferink-Gemser et al., 2004a; 2004b). By comparing the test results of each player with these reference data, it is possible to acknowledge strong and weaker performance characteristics, and, consequently, use this information in training.